The Development of Space Surveillance Settlement Concept in Pesantren Gadingmangu Perak Jombang - Kurniadi Kurniadi; Arif Jauhar Tontowi; Eko Wahyudi (SPECTA Journal of Technology, 2017)
The existence of Gadingmangu Pesantren in the middle of the global can become one of the interesting object to study, considering that this pesantren is improved of education area. Since the beginning of this pesantren, they have lived in harmony with the community. If observed, there is a strong will to protect traditional culture in the middle of the global culture this day.There are three problem which considered in this research. First is to see how the interaction process between the pesantren and the surrounding societies, and which space and environment setting have a function as media for social interaction between the pesantren and the neighbourhood. Second, how is the attitude and behavior of the community about the existence of Gadingmangu Pesantren settlement. The aims of this study is to see cultural values of pesantren which used in the settlement.Methodology used is field research to study physical and non physical aspect intensively. Area of architecture, environment psychology, and sociology, covers settlement and cultural values of pesantren at Gadingmangu. The research results is to find the concept of space surveillance settlement can be considered by physical aspects. Physically, there is a setting which reflect strong interaction between the pesantren Gadingmangu and the settlement nearly.